Genetic analysis of 56 polymorphisms in 17 genes involved in methionine metabolism in patients with abdominal aortic aneurysm. Issue 11 (17th July 2008) - Giusti, B; Saracini, C; Bolli, P; Magi, A; Sestini, I; Sticchi, E; Pratesi, G; Pulli, R; Pratesi, C; Abbate, R
Abstract : Background: Previous studies suggested an association between abdominal aortic aneurysm (AAA) and hyperhomocysteinaemia, a complex trait determined by genetic and environmental factors. Our hypothesis was that polymorphisms in genes directly or indirectly involved in methionine metabolism may contribute to AAA susceptibility. Method: We studied 56 polymorphisms in MTHFR, MTR, MTRR, CBS, MTHFD1, SLC19A1, NNMT, TCN2, AHCY, BHMT, BHMT2, FOLH1, TYMS, ENOSF1, SHMT1, PON1, PON2 genes according to their demonstrated/putative function, localisation in promoter or regulatory and coding regions and/or heterozygosity values >0.300. Polymorphisms were evaluated by using a primer extension based microarray technology in 423 AAA patients and 423 matched controls. Results: All polymorphisms resulted in Hardy–Weinberg equilibrium in patients and controls. At the multiple logistic regression analysis adjusted for traditional cardiovascular risk factors (sex, age, hypertension, smoking habit, dyslipidaemia, diabetes) and chronic obstructive pulmonary disease (COPD), rs8003379 MTHFD1 (odds ratio (OR) 0.41, 95% confidence interval (CI) 0.26 to 0.65) and rs326118 MTRR (OR 0.47, 95% CI 0.29 to 0.77) polymorphisms resulted in independent susceptibility factor for AAA. Conclusions: After haplotype reconstruction, logistic regression analyses adjusted for traditional risk factors and COPD showed a significant association among AAA and AHCY, FOLH1, MTHFD1, MTR, NNMT, PON1 and TYMS haplotypes. Our findings offer new insights into the pathogenesis of AAA.